2012
DOI: 10.1002/eji.201242683
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and natural infections in MyD88‐ and IRAK‐4‐deficient mice and humans

Abstract: Most Toll-like-receptors (TLRs) and interleukin-1 receptors (IL-1Rs) signal via myeloid differentiation primary response 88 (MyD88) and interleukin-1 receptor-associated kinase 4 (IRAK-4). The combined roles of these two receptor families in the course of experimental infections have been assessed in MyD88- and IRAK-4-deficient mice for almost fifteen years. These animals have been shown to be susceptible to 46 pathogens: 27 bacteria, 8 viruses, 7 parasites, and 4 fungi. Humans with inborn MyD88 or IRAK-4 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
124
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 133 publications
2
124
3
1
Order By: Relevance
“…In vivo studies have shown survival to be higher for Irak1 −/− , Irak2 −/− , and Irak4 −/− mice following LPS injection (Irak3 −/− mice were not tested) (11,38,39) and lower for Irak1 −/− and Irak4 −/− mice (the only two strains tested) following Staphylococcus aureus infection (11,40). Myd88 −/− mice and, by inference, Irak4 −/− mice are susceptible to many other pathogens not used for the inoculation of the other mutants (41). Overall, these studies suggest that the mouse IRAK-1, IRAK-2, and IRAK-4 proteins play activating roles in TLR and IL-1R responses and protective immunity to bacteria, albeit to different degrees, whereas IRAK-3 seems to have an inhibitory effect (34,42).…”
Section: Significancementioning
confidence: 95%
See 2 more Smart Citations
“…In vivo studies have shown survival to be higher for Irak1 −/− , Irak2 −/− , and Irak4 −/− mice following LPS injection (Irak3 −/− mice were not tested) (11,38,39) and lower for Irak1 −/− and Irak4 −/− mice (the only two strains tested) following Staphylococcus aureus infection (11,40). Myd88 −/− mice and, by inference, Irak4 −/− mice are susceptible to many other pathogens not used for the inoculation of the other mutants (41). Overall, these studies suggest that the mouse IRAK-1, IRAK-2, and IRAK-4 proteins play activating roles in TLR and IL-1R responses and protective immunity to bacteria, albeit to different degrees, whereas IRAK-3 seems to have an inhibitory effect (34,42).…”
Section: Significancementioning
confidence: 95%
“…Human patients with autosomal-recessive complete IRAK-4 or MyD88 deficiency have a common clinical phenotype, characterized by extreme susceptibility to a small range of pyogenic bacterial infections, with normal resistance to other bacteria and most viruses, fungi, and parasites (41,43). IRAK-4-and MyD88-deficient patients present with meningitis, sepsis, arthritis, osteomyelitis, and deep inner-organ/tissue abscesses, mostly caused by gram-positive Streptococcus pneumoniae and S. aureus and, more rarely, by gram-negative Pseudomonas aeruginosa and Shigella sonnei .…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the majority of studies relied on MyD88-deficient experimental systems (5,12). In humans, IRAK-4 deficiency is related to increased susceptibility to invasive pyogenic infections (13).…”
mentioning
confidence: 99%
“…However, the clinical condition usually improves with age, such that IRAK-4 deficiency is life-threatening in infancy and early childhood but almost harmless in adulthood. This suggests that acquired immunity progressively compensates for the deficient innate immunity (12,14). Additionally, IRAK-4 polymorphism is associated with an increased risk for severe sepsis and cancer initiation, as well as tumor progression and therapy resistance (10,15).…”
mentioning
confidence: 99%